Theory of Provocation In Light of Political Science - Karwat, Mirosław (Studies in Politics, Security and Society, 2022)
The present volume discusses the subject of provocation and its various applications in the field of political science. Provocation itself combines the artificial induction of events, attitudes and human behavior, and the unilateral prejudging of issues, resulting in the interlocutor being surprised, trapped, manipulated or extorted. A political provocation manifests itself in various forms: productive or parasitic; pointed, collective or networked influence; initiative or reactive and reflexive; causal, deceptive or discrediting; constructive or destructive. The author brings forth real-world examples to illuminate the various intricacies of this concept, its applications, aims, and much more.